Ellie and the harpmaker [large type] - Prior, Hazel (Thorndike Press large print basic, 2019)
Dan Hollis lives a happy, solitary life carving exquisite Celtic harps in his barn in the countryside of the English moors. Here he can be himself, away from social situations that he doesn't always get right or completely understand. On the anniversary of her beloved father's death, Ellie Jacobs takes a walk in the woods and comes across Dan's barn. She is enchanted by his collection. Dan gives her a harp made of cherrywood to match her cherry socks. He stores it for her, ready for whenever she'd like to take lessons. Ellie begins visiting Dan almost daily and quickly learns that he isn't like other people. He makes her sandwiches precisely cut into triangles and repeatedly counts the (seventeen) steps of the wooden staircase to the upstairs practice room. Ellie soon realizes Dan isn't just different; in many ways, his world is better, and he gives her a fresh perspective on her own life.